Preliminary Studies on the Synthesis of (–)-Shikimic Acid Based 1,2,3,4-Tetrahydrobenzo[b]phenanthridine-7,12-diones - Cuellar, Mauricio A.; Quiñones, Natalia; Vera, Viviana; Salas, Cristian O.; Estévez, Juan C.; Estévez, Ramón J. (Synlett, 2015)
Six new angucyclinone aza-analogues containing an embedded shikimic acid moiety have been prepared by a synthetic sequence involving the construction of their tetracyclic framework by a regiocontrolled hetero-Diels–Alder reaction of shikimic acid derived 1-azadiene 7- and 2-haloquinones.
Keywords: (–)-shikimic acid; angucyclinone analogues; aza-Diels–Alder reaction; 2-bromoquinones